Sengketa Merek Dagang Geprek Bensu dalam Perspektif Hukum Hak Kekayaan Intelektual - Komang Cahyaniarsa Suryaningrat; Ni Komang Irma Adi Sukmaningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
Intellectual property rights (IPR) are an important legal tool for trademark ownership, protecting business quality, and protecting a company's economic interests. Consumers build trust in trademarks because they signal distinct product quality and reflect a positive and consistent corporate image. Trademark protection is regulated by national law under Trademark Law No. 20 of 2016, which provides legal certainty for trademark owners. This law stipulates that a trademark is only valid if it has distinctive elements, is not imitative, and has been officially registered with an authorized institution. The